BILIMLENDIRIW SISTEMASÍNDA FIZIKADAN MÁSELELER SHESHIWDIŃ HÁR TÚRLILIGI - Jaksimuratov, I.J.; Otarbaev, A.E.; Hajibaev, D.G.; Jaksimuratova, Z.J.; Kadirov, R.SH. (SCIENCE and SOCIETY, 2021)
This article provides information on classifications and problem solutions from a physics course. Different ways of solving the same problem are shown. They talk about the importance of problem solving and its benefits for young researchers.